Border Catholic Schools: Unique Stakeholder Alliances (Part I) - Watt, Karen M. (Catholic Education: A Journal of Inquiry and Practice, 2002)
This article, the first of a two-part series, presents an analysis of data extracted from the dissertation The Impact of Catholic Schooling on Low-Income Mexican-American Students (Watt, 1999). The research was prompted by the author’s interest in The Coleman Report of 1966, a controversial document that claimed multiply-disadvantaged minority Catholic school students outperformed their public school counterparts. This study was qualitative in nature, exploring four case studies of 3rd-grade teachers, their schools, and their classrooms in a Hispanic cultural context. Findings will be presented in Part II.